Albedo‐Enabled Enhanced Energy Harvesting via GaAs Bifacial Thin‐Film Solar Cells. Issue 7 (24th February 2022) - Xing, Zhang; Nam, Seonghyun; Kim, Dahee; Baek, Yongmin; Kim, Dohyun; Park, Youngseo; Lee, Hsin-Ying; Lee, Ching-Ting; Lee, Kyusang; Heo, Junseok
Abstract : In addition to direct solar illumination to the photovoltaic cell, the albedo effect provides a unique opportunity to enhance energy harvesting. However, conventional solar cells are inefficient albedo energy harvesters because the rear side of the cell is usually blocked by a thick substrate or metal contact. In this study, structurally thin active layers of GaAs thin‐film solar cells covered with transparent Ag nanowires that enable bifacial solar cell operations are fabricated. The GaAs bifacial thin‐film solar cell is fabricated by bonding the active regions of the solar cell on colorless polyimide sheets with highly transparent epoxy adhesives. The fabricated bifacial solar cells without any anti‐reflection coatings demonstrated power conversion efficiencies of 8.54 and 6.78% at the front and rear sides, respectively, under AM 1.5 G irradiance conditions. The increase in energy harvesting by the GaAs bifacial thin‐film solar cells was estimated, which showed approximately a 72% increase in short‐circuit current density ( J SC ) when the solar cells operated on a high‐reflection‐coated ground. Positioning the solar cells on snow or sand (deserts and beaches) increased J SC by ≈44 and 31%, respectively, compared to monofacial solar cells. Abstract : Structurally thin active layers of GaAs thin‐film solar cells covered with transparent Ag nanowires that enable bifacial solar cell operations are fabricated. The albedo effect boosting the energy harvesting by the GaAs bifacial thin‐film solar cells is estimated to be 72% increase in the short‐circuit current density ( J SC ) when the solar cells operate on a high‐reflection‐coated ground.